Central Clearing and Asset Prices - Albert J. Menkveld; Emiliano Pagnotta; Marius A. Zoican (Tinbergen Institute, 2013)
We investigate the effects of introducing a central clearing counterparty (CCP) on securities prices by adopting as an experimental construct the 2009 CCP reform in three Nordic markets. We find that, relative to other European economies, these countries experience market-adjusted equity returns of -1.08% per month during a 16-month announcement window. We also find negative effects on price-earnings ratios. The decrease in prices is less pronounced for stocks with low number of counterparties and,consistent with the margin-CAPM, more pronounced for stocks with higher margins. Our results suggest that introducing a CCP may have unintended negative consequences for public corporations.
Keywords: G12; G14; G23; 330; clearing; asset prices; margins; liquidity